DESIGN AND IMPLEMENTATION OF A WEB-BASED ELECTRONIC SUPPLY CHAIN MANAGEMENT SYSTEM FOR SEWING MATERIAL INVENTORY MANAGEMENT IN THE GARMENT INDUSTRY - Kalsumi; Riki Andri Yusda; Mustika Fitri Larasati (Jurnal Sistem Informasi, 2026)
The development of information technology encourages small businesses to adopt digital systems to improve operational efficiency and data management. However, many small-scale garment businesses still rely on manual inventory management processes, which often result in data inconsistencies, delays in reporting, and inefficient coordination. This study aims to develop a web-based Electronic Supply Chain Management (E-SCM) system to improve inventory control and operational performance. The research applies the Software Development Life Cycle (SDLC) using the Waterfall model, which includes requirement analysis, system design, implementation, testing, and evaluation. Data collection was conducted through observation and interviews, while system testing was performed using the Black Box Testing method. The results show that the implementation of the system significantly improves operational efficiency. The time required to generate inventory reports decreased from approximately 60 minutes to 10 minutes (an improvement of 83%), while stock data accuracy increased from 85% to 95%. In addition, stock discrepancies were reduced from 15% to 5%, indicating better data consistency and control. This study contributes by providing an integrated E-SCM model combined with measurable performance indicators for small-scale garment businesses. The findings imply that the adoption of the proposed system can enhance efficiency, accuracy, and decision-making in inventory management.   Keywords: E-SCM, Inventory System, SDLC, Web-Based System, Supply Chain Management.